The effect of γ-FeOOH on enhancing arsenic adsorption from groundwater with DMAPAAQ + FeOOH gel composite - Safi, Syed Ragib (Sci Rep, 2019)
Arsenic contamination of groundwater is a serious concern worldwide. The research gaps in removing arsenic are selectivity, regeneration and effective removal rate at neutral pH levels. In this study, we discussed the reasons of the high arsenic adsorption from groundwater of our previously developed adsorbent, a cationic polymer gel, N,N-dimethylamino propylacrylamide, methyl chloride quaternary (DMAPAAQ), loaded with iron hydroxide. We used a transmission electron microscope (TEM) and thermogravimetric analyser (TGA) to detect the iron contents in the gel and ensure its maximum impregnation. We found that the gel contains 62.05% FeOOH components. In addition, we used the Mössbauer spectroscopy to examine the type of impregnated iron in the gel composite and found that it was γ-FeOOH. Finally, we used Fourier transform infrared spectroscopy (FTIR) to examine the surface functional groups present in the gel and the differences in those groups before and after iron impregnation. Similarly, we also investigated the differences of the surface functional groups in the gel, before and after the adsorption of both forms of arsenic. To summarize, this study described the characteristics of the gel composite, which is selective in adsorption and cost effective, however further applications should be investigated.